2008
DOI: 10.1007/s10562-008-9574-6
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Hydrogenation of Nitrate to Harmless Compounds in Water Over Copper–Palladium Bimetallic Clusters Supported on Active Carbon

Abstract: Cu-Pd bimetallic clusters with a Cu/Pd atomic ratio of 2 supported on active carbon (AC) ([Cu 2 -Pd] cluster / AC) selectively hydrogenated nitrate ions in water to harmless compounds, including N 2 and N 2 O ([99% selectivity), and the formation of NH 3 was suppressed to tolerable levels (\.5 ppm). The activity and selectivity of [Cu 2 -Pd] cluster /AC were superior to that of conventionally prepared Cu-Pd/AC. [Cu 2 -Pd] cluster /AC showed stationary conversion and selectivity from the onset of the reaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…On the other hand, if the ratio is low, the selectivity will be low. We have demonstrated that the selectivity for N 2 + N 2 O increases with a decrease in the partial pressure of H 2 over Cu-Pd bimetallic clusters supported on AC [14].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, if the ratio is low, the selectivity will be low. We have demonstrated that the selectivity for N 2 + N 2 O increases with a decrease in the partial pressure of H 2 over Cu-Pd bimetallic clusters supported on AC [14].…”
Section: Resultsmentioning
confidence: 91%
“…2) is a critical problem, because the allowable level of NH 3 in drinking water is 0.5 ppm. Many studies have been carried out on the catalytic reduction of NO 3 -using bimetallic catalysts, such as Cu-Pd [3][4][5][6][7][8][9][10][11][12][13][14], Sn-Pd [15][16][17], In-Pd [9,18], and Cu-Pt [19,20], since Vorlop and coworkers discovered that Cu-Pd/Al 2 O 3 is an active and selective catalyst [3,4]. [7].…”
Section: Introductionmentioning
confidence: 99%
“…The local concentrations of both NO 3 -and H 2 have been shown to be a key operating condition to maintain low levels of NH 3 during catalytic NO 3 -reduction [5, 9,18]. In an attempt to minimize NH 3 production, influent concentrations of 1.4 mM NO 3 -and 1.95 mM H 2 were used ( Fig.…”
Section: Hydrogen Concentrationmentioning
confidence: 99%
“…However, nitrate overload from anthropogenic sources can lead to contaminated drinking water in which the nitrate level exceeds the legal limit (USEPA MCL, 714 lM) [1]. The use of Pd-based heterogeneous catalysts with hydrogen as the electron donor has emerged as an attractive treatment strategy for nitrate-contaminated water [2], but the issues of selectivity (formation of significant amounts of ammonia as well as nitrogen) [2][3][4][5][6][7][8][9][10][11] and sustainability (activity maintenance when confronted with potential foulants in the source water) [10,11] remain formidable barriers to widespread adoption. We have examined how three critically important solution conditions affect the operation of a Pd-In/c-Al 2 O 3 catalyst for nitrate reduction: (i) the concentration of dissolved oxygen (DO), an alternative electron acceptor to nitrate, (ii) the specific NO 3 -:H 2 influent loading; and (iii) the presence of a known foulant, sulfide.…”
Section: Introductionmentioning
confidence: 99%
“…However, they show high activity in the reduction of nitrites [3][4][5][12][13][14]. Among the studied bimetallic systems, palladium systems promoted with Cu, Sn, Ag or Fe supported on different kinds of oxide carriers [14][15][16][17][18][19][20], polymers [21,22], zeolites [23], active carbons [24][25][26], resin [27][28][29], showed the best catalytic characteristics. The mechanism of these systems has not been explained unequivocally yet.…”
Section: Introductionmentioning
confidence: 99%